2011
DOI: 10.1371/journal.pone.0019913
|View full text |Cite
|
Sign up to set email alerts
|

Litter Size Variation in Hypothalamic Gene Expression Determines Adult Metabolic Phenotype in Brandt's Voles (Lasiopodomys brandtii)

Abstract: BackgroundEarly postnatal environments may have long-term and potentially irreversible consequences on hypothalamic neurons involved in energy homeostasis. Litter size is an important life history trait and negatively correlated with milk intake in small mammals, and thus has been regarded as a naturally varying feature of the early developmental environment. Here we investigated the long-term effects of litter size on metabolic phenotype and hypothalamic neuropeptide mRNA expression involved in the regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 55 publications
1
5
0
1
Order By: Relevance
“…With a good agreement with our results, Bronson reported that there is no support for the hypothesis that an increase in body fat and thus an increase in circulating leptin trigger puberty in female mice [14]. Also, thyroid hormones are essential for photoinduced egg production [15] as well as being important for growth and development in vertebrates [16]. In the present study, photo-induced earlier egg production in hens was not accompanied the changes of thyroxine (T 4 ).…”
Section: Discussionsupporting
confidence: 75%
“…With a good agreement with our results, Bronson reported that there is no support for the hypothesis that an increase in body fat and thus an increase in circulating leptin trigger puberty in female mice [14]. Also, thyroid hormones are essential for photoinduced egg production [15] as well as being important for growth and development in vertebrates [16]. In the present study, photo-induced earlier egg production in hens was not accompanied the changes of thyroxine (T 4 ).…”
Section: Discussionsupporting
confidence: 75%
“…The previous studies showed that maternal energy or nutritional changes would influence energetic strategies and reproductive fitness (Lou et al, 2013;Watkins and Sinclair, 2014;Zhang et al, 2011aZhang et al, , 2011b. Maternal high-protein diet resulted in a small increase in digestible energy intake at peak lactation in Brandt's voles (Lou et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the hyperphagia of SL rats can be explained by both the leptin resistance (Rodrigues et al 2009, Zhang et al 2011) and the higher NPY in the ARC. Previously, Plagemann and coworkers (1999) have shown that SL rats have higher NPY-immunopositive neurons at weaning, explaining their higher food intake since weaning.…”
Section: Hormones and Adipose Tissue Dysfunctionmentioning
confidence: 99%